Econometric gravity models of mutual trade of the EAEU countries - Gospodarik, Catherine G.; Maenova, Elena S. (Journal of the Belarusian State University. Economics, 2021)
The article analyses the foreign trade activity of the Republic of Belarus on the basis of the econometric gravity model of foreign trade of the EAEU member states. In addition, the export potential of the Republic of Belarus was analysed, as well as the comparative advantages of Belarus in trade with the EAEU member states were given. Based on the analysis, the authors offer recommendations for increasing export potential.